Improving Student Learning Outcomes In Fractional Theme Using Discussion Method In Class V At Sd Negeri 076731 Teluk Limo, South Nias District - Berkati Lugu; Muhammad Ali Akbar (International journal of technology and education research, 2023)
This study aims to determine the application method discussion to increase students ' understanding of fractional material in grade V SD COUNTRY N o . 076731 Teluk Limo, PP Batu Utara District , Regency South Nias . This study uses process assessment, assessment of student learning outcomes and reflection on learning by the teacher. This research was conducted in elementary school COUNTRY N o . 076731 Teluk Limo, PP Batu Utara District Regency South Nias in Mathematics subject. The research subjects were 20 grade V students consisting of 9 boys and 11 girls. When the research was conducted in April 2023 (starting from preparatory activities to implementing actions). From the results of the study the authors made observations of 2 cycles, where at the pre-cycle stage only 8 (40%) students who complete learning. Seeing this fact, the writer made learning improvements at the stage of cycle I. At this stage, the classical completeness of student learning was 70%, which means that there were 14 students who were included in the complete category, so that students could achieve the KKM score that had been set, which was 85%, so the writer did improvement of learning in cycle II by using the discussion method and it turned out that satisfactory results were obtained for all 20 students who had completed the expected KKM scores. For this reason, learning improvement research ends in cycle II.